In-e-qualities, Regulation, Ethics & Records - reflections from a case in Online Trade - Engvall, Tove (Archives of Business Research, 2018)
In an ethnographic study in online trade at the financial market, different forms of inequalities in client-broker/business relations have been found. It takes expression in for example design of technology, control of and access to information, competence and misuse of trust. Trust is at the center of concern, since that is crucial both to success and a risk for being taken advantage of. This relates to power between actors, responsibilities and accountability. This is where records role as evidence of human acts and conducts have a central role, both in relation to regulation and business ethics. As established structures for ensuring rights and obligations throughout societies are challenged by digitalization and globalization, this has to be recreated in the online context. The article conclude that both regulation and ethics are crucial in forming common values, behaviours and understanding of trust. If not, trust is easily violated which set people in trouble. In order to ensure trust, accountability is an important factor to consider, as well as informal means for ensuring fair behaviours that promotes the building and maintenance of trust among actors. As the technological development challenge processes and means for trust and accountability, new tools ought to be developed. As well as people-related aspects at both personal, business and societal level have to be considered.